Integration and conditional convergence in the enlarged EU area - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2004)
Using pooled mean-group estimation we first analyse conditional convergence in the EU15 area in 1960-2002. Conditional convergence is well documented for the EU15 countries and deeper European integration is mostly shown to have fastened convergence. Also higher investment, lower public consumption and lower inflation have increased GDP growth. Then we apply the same method in order to estimate the conditional convergence of the new EU member countries of Central and Eastern Europe towards the average of the EU15 countries since 1993. The CEE8 countries are shown to have converged conditionally towards the EU15 countries' average level of GDP per labour force. – – Tässä tutkimuksessa analysoidaan ensin, kuinka ehdollinen konvergenssi on edistynyt EU15-alueella vuosina 1960-2002. Ehdollista konvergenssia osoitetaan tapahtuneen, ja syvempi integraatio on enimmäkseen edistänyt sitä. Myös korkeampi investointiaste sekä pienempi julkinen kulutus ja alempi inflaatio ovat nopeuttaneet talouskasvua. Sitten käytämme samaa menetelmää (PMG, pooled mean group) analysoidaksemme kahdeksan Keski- ja Itä-Euroopan uuden EU-maan konvergenssia kohti EU15-maiden keskimääräistä BKT per työvoima-tasoa vuosina 1993-2002. KIE8-maiden osoitetaan konvergoituneen ehdollisesti kohti EU15-maiden keskiarvoa tässä suhteessa.
Keywords: 330; EU; enlargement; economic integration; economic growth; conditional convergence; EU; itälaajeneminen; taloudellinen integraatio; talouskasvu; ehdollinen konvergenssi; EU-Erweiterung; Wirtschaftsintegration; Wirtschaftswachstum; Entwicklungskonvergenz; Schätzung; EU-Staaten